A novel comprehensive utilization of vanadium slag/epoxy resin/antimony trioxide ternary composite as gamma ray shielding material by MCNP 6.2 and BXCOM - Kavanoz, H. Birtan; Akcali, Ozgur; Toker, Ozan; Bilmez, Bayram; Caglar, Mustafa; Icelli, Orhan (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
New research on composite materials was proposed for both gamma ray shielding and fireproofing. When compared to concrete, composite materials show up higher shielding properties in the 0.015 MeV-15 MeV incident energy range. The composite was prepared with vanadium slag, epoxy resin and antimony-trioxide. Different ratios of ternary composite were investigated in order to determine the optimum ratio for shielding and anti-flame properties. Photon atomic parameters with shielding were determined by BXCOM and MCNP 6.2. BXCOM program determines the buildup factors (both EBF and EABF) in the 0.015-15 MeV energy range for up to 40 mean free path (mfp) penetration depth. It uses geometric progression (G-P) fitting method. The effective electron number (N-eff) and the effective atomic number (N-eff) were also obtained with the BXCOM software. Furthermore, parameters such as the mass attenuation coefficients (mu/rho), half-value layer (HVL) and tenth-value layer (TVL) were determined by MCNP 6.2 in order to confirm and compare with WinXCOM results. Obtained results may be concluded to have preferable shielding properties for the composite as an alternative to concrete. Antimony-trioxide (x = 0.03), was found to exhibit the minimum EBF and EABF values, and is a convenient radiation shielding material. The Epoxy resin-vanadium slag and antimony-trioxide ternary glassy composite indicates better radiation shielding properties than concrete, but weaker than lead.
Keywords: Buildup factor; BXCOM; Mass attenuation coefficient; MCNP 6.2; Shielding; STRUCTURAL-PROPERTIES; BUILDUP FACTORS; GLASSES; SLAG; Chemistry; Nuclear Science & Technology; Physics